MELACAK JEJAK AWAL INDIANISASI DI PANTAI UTARA JAWA TENGAH - Sofwan Noerwidi (Berkala Arkeologi, 2007)
From a geographic point of view, the Archipelago lies at a strategic crossroads between continents and oceans. Under these conditions, the development of culture in these islands has always been influenced by the major cultures around it, namely India and China. One problem of cultural history that is still a mystery is the process of the entry of Indian Culture in Central Java, namely the entrance and route of Indianization to the interior of southern Central Java. One of the areas on the north coast of Central Java which is quite strategic from a geographical point of view is Batang Regency. Based on its potential, it can be estimated that Batang Regency has a strategic role in the process of entering and developing the influence of Indian Culture on the Island of Java.